Re-orientation and integration of the classical and interspecific linkage maps of the long arm of tomato chromosome 7 - Burbidge, Alan; Lindhout, P.; Grieve, T. M.; Schumacher, Karin; Theres, K.; van Heusden, A. W.; Bonnema, A. B.; Woodman, K. J.; Taylor, I. B. (Theoretical and applied genetics, 2001)
To obtain reliable classical and integrated interspecies maps of the long arm of chromosome 7 of tomato, detailed mapping work was undertaken and several phenotypic and molecular markers were assigned loci on both maps to provide reliable cross-reference points. To maximise the value of the new maps, pair-wise segregation data for classical genetic markers from the literature were included, based on large segregating populations with readily scorable phenotypes. In addition, to increase confidence in these maps, introgression lines were used to confirm important map locations. The revised classical map is based on two- and three-point test-cross data from a number of F2 and BC1 mapping populations. The integrated interspecies map is based on F2 mapping populations derived from crosses of Lycopersicon esculentum with Lycopersicon pennellii (LA716). The genetic analyses for both maps were performed using the computer package JoinMap. The revised composite classical map indicates that some of the map positions reported in the literature are incorrect. The linear order of the classical markers common to both the revised classical and integrated interspecies maps are in complete agreement. Production of the integrated interspecies map resulted in re-orientation of the existing molecular map.